INVESTIGATE THE CORRELATION OF SCIENCE LEARNING INTEREST ON SCIENCE PROCESS SKILLS THROUGH SCIENTIFIC APPROACH - Lisa Ariyanti Pohan; Tuti Hardianti; Wildawani Siregar (Journal Of Educational Experts (JEE), 2021)
In this study, the learning process was carried out using a scientific approach, then measuring the students' interest in science lessons and science process skills. This study aims to: 1) Determine the level of student interest in science lessons using a scientific approach, 2) Investigate the effect of the scientific approach on students' science process skill levels, 3) Investigate the relationship between interest in science lessons and science process skills. The research method used in this study is descriptive and associative correlational survey research methods. The instruments used in this study consisted of 1) questionnaire on the level of students' interest in science, 2) interview sheets, 3) Science Process Skills Test. The samples of this research were 45 students of AnNizam grade VII. The results showed that the investigation of the majority level of student interest was 52% at a high level, the results of examining the effect of scientific learning on process skills using the independent sample t-test obtained tcount > ttable, namely 6.16 > 1.68. The simple regression investigation found a strong relationship between interest and science process skills of about 0.63.